2014
DOI: 10.1088/0004-637x/794/1/32
|View full text |Cite
|
Sign up to set email alerts
|

Helioseismology and Asteroseismology: Looking for Gravitational Waves in Acoustic Oscillations

Abstract: Current helioseismology observations allow the determination of the frequencies and surface velocity amplitudes of solar acoustic modes with exceptionally high precision. In some cases, the frequency accuracy is better than one part in a million. We show that there is a distinct possibility that the quadrupole acoustic modes of low order could be excited by gravitational waves (GWs), if the GWs have a strain amplitude in the range 10 −20 h −20 with h −20 ∼ 1 or h −20 ∼ 10 3 , as predicted by several types of G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…Futhermore, it is in principle possible that the (gigantic) burst of dark photons affects nearby (hidden-) charged stars, via the same mechanisms we described. In such a case, a passing burst of hidden radiation would cause nearby stars to oscillate, with r.m.s fluctuations that could be measurable and extracted from asteroseismology studies, in a phenomena similar to that described recently for GWs [77,78].…”
Section: Discussion and Final Remarksmentioning
confidence: 60%
“…Futhermore, it is in principle possible that the (gigantic) burst of dark photons affects nearby (hidden-) charged stars, via the same mechanisms we described. In such a case, a passing burst of hidden radiation would cause nearby stars to oscillate, with r.m.s fluctuations that could be measurable and extracted from asteroseismology studies, in a phenomena similar to that described recently for GWs [77,78].…”
Section: Discussion and Final Remarksmentioning
confidence: 60%
“…Modern examinations of Earth's higher harmonics [18] and crust excitations [19][20][21] may also be interesting, but likely have worse strain sensitivity. Lunar [22] as well as asteroseismic observations [23][24][25] have shown more promise towards detecting (quadrupole) metric variations; monopole strain excitations of these systems merit further investigation.…”
mentioning
confidence: 99%
“…In the third and fourth papers [37,38], based on their earlier theoretical work, they showed that asteroseismology can place upper bounds on the amplitude of a stochastic background of GWs in the mHz and µHz frequency range. Recently, Lopes and Silk [39][40][41] and Lopes [42] published studies on the stars quadrupole acoustic modes. They showed that GWs with a strain spectral amplitude in the range 10 −20 -10 −17 can lead to the excitation of Sun's low order quadrupole acoustic modes [39].…”
Section: Introductionmentioning
confidence: 99%